2008
DOI: 10.1902/jop.2008.070431
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Prosthetic Management of Interproximal Region With Single‐Implant Restorations: 1‐Year Prospective Study

Abstract: The combination of surgical and prosthetic plans represents the key factor to optimize predictability in single-implant esthetics. The recommended interproximal distance between the implant and the adjacent tooth is 2.5 to 4 mm. The distance from the contact point to the interdental bone is recommended to be <7 mm. Papilla presence is also correlated with a thick gingival biotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 23 publications
4
99
1
Order By: Relevance
“…For aesthetic reasons and proper appearance of the interproximal papilla, an interimplant and an interimplant-tooth distances of 3 mm and 3 to 4 mm have been recommended, respectively. 28- 31 A thin soft tissue biotype of ,2-mm thickness has often been associated with thinner underlying bone, angular bone defects, increased susceptibility to the loss of papilla after immediate implant placement, and is more prone to recession in response to trauma and bacteria than a thick biotype. 32 Consequently, a thin soft tissue biotype affects the implant success, particularly when immediate loading is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…For aesthetic reasons and proper appearance of the interproximal papilla, an interimplant and an interimplant-tooth distances of 3 mm and 3 to 4 mm have been recommended, respectively. 28- 31 A thin soft tissue biotype of ,2-mm thickness has often been associated with thinner underlying bone, angular bone defects, increased susceptibility to the loss of papilla after immediate implant placement, and is more prone to recession in response to trauma and bacteria than a thick biotype. 32 Consequently, a thin soft tissue biotype affects the implant success, particularly when immediate loading is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…A maximum value was observed in the P1 maxillary incisors, while a minimum was found in the B1 maxillary central incisors, confirming that the force tolerance for the bite force in the P1 maxillary central incisors was weaker than that in other types, and the force tolerances of the B1 and B2 incisors were relatively good [11]. In addition, the analysis of the equivalent stresses at the four lines showed that the M1 and P1 maxillary central incisors showed a sudden decrease in the buccal, lingual, mesial, and distal equivalent stresses at 1-19 mm below the CEJ, while the change from the 2 mm below the CEJ to the apex was gradual, with a sharply declining trend in the higher position.…”
Section: Discussionmentioning
confidence: 61%
“…The mandibular database for the Chinese population shows that the maxillary central incisor differs inside the alveolar bone [4,11]. Its major axis and the maxillary major axis are generally neither in the same direction nor parallel.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Miller gingival recession classification [3], gingival recession was classified: Class I, gingival recession does not exceed the mucogingival junction, no loss of bone or soft tissue is observed in adjacent tooth space; Class II, gingival recession exceeds the mucogingival junction, no loss of bone or soft tissue is observed in adjacent tooth space; Class III, gingival recession does not exceed the mucogingival junction, and there is a loss of periodontal tissue in adjacent teeth; Class IV, gingival recession exceeds the mucogingival junction, and there is a loss of periodontal tissue in adjacent teeth. We used probing transparency in the sulcus [12] to determine gingival biotype.…”
Section: Data Collectionmentioning
confidence: 99%